1976
DOI: 10.1097/00000658-197609000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Acute Traumatic Rupture of the Aorta

Abstract: Forty-three patients with aortic rupture secondardy to blunt trauma have been treated at the University of Micigan within the past 10 years with an overall salvage rate of 70%. The diagnosis should be suspected in anyone who has sustained a high speed decelerating injury, if the chest roentgenogram shows media-stinal widening, whether or not there is hypertension of the upper extremities; systolic murmur, or external evidence of chest injury. Aortography should be employed to confirm the diagnosis and to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
6

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(47 citation statements)
references
References 31 publications
3
38
0
6
Order By: Relevance
“…It should also resolve with a larger injection volume. Ductus diverticulum, a remnant of the ductus arteriosus, can mimic a traumatic pseudoaneurysm.Z14, 21 Richardson et al 23 reported one such case in which CT helped confirm the absence of aortic injury at the site in question. In most cases, CT is able to differentiate between aortic tortuosity, atherosclerotic aneurysm, and dissecting hematoma,13 particularly when used in conjunction with the arteriogram.…”
Section: Resultsmentioning
confidence: 99%
“…It should also resolve with a larger injection volume. Ductus diverticulum, a remnant of the ductus arteriosus, can mimic a traumatic pseudoaneurysm.Z14, 21 Richardson et al 23 reported one such case in which CT helped confirm the absence of aortic injury at the site in question. In most cases, CT is able to differentiate between aortic tortuosity, atherosclerotic aneurysm, and dissecting hematoma,13 particularly when used in conjunction with the arteriogram.…”
Section: Resultsmentioning
confidence: 99%
“…Although a completely normal chest radiograph has a 98±99 % negative predictive value for traumatic aortic injury [7,10,39], it must be kept in mind that in some cases of acute aortic traumatic injury, the chest roentgenogram can be normal [14,43], and the radiograph must be taken in the overall context of the patient's injury and symptoms. A high clinical suspicion of thoracic outlet trauma based on the mechanism of the injury dictates a requirement for CTA or catheter-directed thoracic aortography.…”
Section: Chest Radiographmentioning
confidence: 99%
“…Most patients with blunt thoracic injury and an abnormal chest radiograph can be evaluated with computed tomographic aortography (CTA) or conventional catheter aortography. The most common site of aortic disruption resulting in an acute thoracic aortic pseudoaneurysm is at the aortic isthmus [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]; the second most common location is just above the aortic valve.…”
Section: Introductionmentioning
confidence: 99%
“…Ninety-five percent of aortic injuries in blunt trauma occur in the thorax just distal to the left subclavian artery, at the junction of the tethered and mobile segments of the aorta. 1 Feczko, in an autopsy case review of 142 blunt injuries of the aorta, noted that only 6% were found in the abdominal segment. 2 Only 10 cases of blunt injuries to the abdominal aorta in the pediatric age group were identified in a review of the English language literature since 1960.…”
mentioning
confidence: 99%